Pertumbuhan Tanaman Stroberi Pada Berbagai Jenis dan Konsentrasi Pupuk Organik Cair dan Urine Sapi Dengan Sistem Hidroponik Irigasi Tetes - Nurlailah Mappanganro (Biogenesis: Jurnal Ilmiah Biologi, 2013)
The research aimed at investigating the effect of the liquid organic fertilizer from the cattle dung towards the growth of the strawberry plant, the effect of the cow urine fermented on the growth of the strawberry plant, and the effect of the liquid organic fertilizer from the cattle dung and cow urine fermented towards the growth of the strawberry plant. The research was designed by using complete randomized design with three replications with 36 treatments of the types and concentrations of the liquid organic fertilizer and cow urine. The result of the research indicates that the cow liquid organic fertilizer gives the best results on the plant height and the number of leaves ofthe strawberry plant, whereas the rabbit liquid organic fertilizer gives the best results on the number of flower on every strawberry plant. The addition of the cow urine (50 mL L-1) gives the best result on the growth of the strawberry plant. The cow liquid organic fertilizer (6 mL L-1) and the cow urine(50 mL L-1) give the best results on the plant height and number of leaves, whereas the rabbit liquid organic fertilizer (6 mL L-1) and the cow urine (50 mL L-1) give the best results on the number of flower of every strawberry plant.Keywords: cattle dun, cow urine, growth of strawbery, liquid organic biofertilizer